PHARMACOVIGILANCE OF RADIOGRAPHIC CONTRAST-INDUCED ADVERSE DRUG REACTIONS IN A TERTIARY CARE HOSPITAL OF SOUTH INDIA - Sd, Inbaraj; R, Sidhu Ganesh; Ns, Muthiah (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The aim of this study was to analyze the nature and incidence of adverse drug reactions (ADRs) to radiographic contrast media (oral and intravenous) reported during a 1Â½ years' period in a tertiary care hospital in South India. Methods: The study was an observational prospective study of ADRs to radiographic contrast media (oral and intravenous) observed during a period of 1Â½ years from July 2014 to October 2015 in Department of Radio Diagnosis at Sree Balaji Medical College and Hospital, Chromepet. The observations were analyzed for demographic profile, frequency, severity, causality, and temporal relationship of contrast administration to the occurrence of ADRs. Results: A total of 33 ADRs were observed for oral and intravenous radiographic contrast media administered for radiographic study for the above-mentioned period. It included 17 (51.5%) males and 16 (48.5%) females. Among the 33 ADRs, 19 (57%) were for oral and intravenous radiographic contrast and 14 (42%) for intravenous radiographic contrast alone. The most frequent ADRs were vomiting and nausea 16 (48%), skin rashes 9 (27%), and thrombophlebitis 9 (27%). As per Naranjo's algorithm and WHO causality assessment, all reactions are probable except in one patient who received intravenous contrast administration was possible. According to the Hartwig severity scale, 23 (69%) reactions were mild, 7 (21%) reactions were moderate, and 3 (9%) reactions were severe. There was no fatality observed. Adverse events required immediate treatment in 22 (66%). Most of the reactions, i.e., 21 (63%) appeared immediately after contrast administration. 12 (36%) reactions appeared within next 30 minutes after contrast administration. Conclusion: The common adverse reactions to radiographic contrast were mild in severity such as nausea, vomiting, skin rashes, and giddiness. Most of the reactions occur immediately after administration of contrast. The causality of majority of the ADRs is probable. Pharmacovigilance is an important tool in detection, reporting and thereby preventing ADRs due to radiographic contrast media.